The Influence Of Entrepreneurial Knowledge, Entrepreneurial Motivation, And Family Environment On Students Entrepreneurial Interest - Wulandari, Melsa; Soleh, Ahmad; Hidayah, Nenden Restu (Universitas Dehasen Bengkulu, 2025)
Entrepreneurship is one of the important factors in increasing economic growth and reducing unemployment rates. Although entrepreneurship education has been implemented in universities, students' interest in entrepreneurship is still relatively low. This is due to a lack of knowledge about entrepreneurship, low motivation to start a business, and minimal support from the family environment. Therefore, research is needed to determine the extent to which these three factors can influence students' interest in entrepreneurship, particularly at Dehasen University Bengkulu. The purpose of this study is to determine whether Entrepreneurship Knowledge, Motivation for Entrepreneurship, and Family Environment have a significant impact on the Interest in Entrepreneurship among Management Program Students at Dehasen University Bengkulu. This study uses a quantitative method. The population of this study is students of Management Study Program at Dehasen University Bengkulu, Class of 2022 and 2023, with a total of 339 students and a sample size of 77 respondents. The sampling technique used in this study is Non-Probability Sampling using purposive sampling. The data collection technique used in this study was a questionnaire. The data obtained was then processed using SPSS (Statistical Products and Services Solutions). The results of the multiple linear regression analysis were the equation Y = 21.110 + 0.665 X1 + 0.273 X2 + 0.661 X3 + 3.223, which describes a positive regression direction, meaning that the variables of Entrepreneurship Knowledge (X1), Entrepreneurial Motivation (X2), and Family Environment (X3) have a positive effect on the Entrepreneurial Interest (Y) of students. The results of the calculation with SPSS 25 show that the coefficient of determination from R Square is 0.686. This means that Entrepreneurship Knowledge (X1), Entrepreneurial Motivation (X2), and Family Environment (X3) influence Entrepreneurial Interest (Y) by 68.6%, while the remaining 31.4% is influenced by other variables not examined in this study. The t-test results at a significance level of 0.05 explain that partially, X1 significantly affects Y with a value of 0.002 < 0.05, X2 significantly affects Y with a value of 0.001 < 0.05, and X3 also significantly affects Y with a value of 0.000 < 0.05. Based on the F test, X1, X2, and X3 simultaneously affect Y with a result of 0.000 < 0.05